1977
DOI: 10.1037/0033-2909.84.5.888
|View full text |Cite
|
Sign up to set email alerts
|

Attitude-behavior relations: A theoretical analysis and review of empirical research.

Abstract: Research on the relation between attitude and behavior is examined in light of the correspondence between attitudinal and behavioral entities. Such entities are defined by their target, action, context, and time elements. A review of available empirical research supports the contention that strong attitude-behavior relations dre obtained only under high correspondence between at least the target and action elements of the attitudinal and behavioral entities. This conclusion is compared with the rather pessimis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

172
3,309
6
169

Year Published

1984
1984
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 5,904 publications
(3,656 citation statements)
references
References 148 publications
172
3,309
6
169
Order By: Relevance
“…The survey used for this study reflects physician attitudes and does not directly measure actual behavior in practice but rather selfreported counseling frequencies via broad response categories. However, research has indicated that attitudes may be among the most important predictors of behavior [37]. Also, since the response rate was only 53%, attitudes and perceptions of non-respondents may have differed from respondents.…”
Section: Discussionmentioning
confidence: 99%
“…The survey used for this study reflects physician attitudes and does not directly measure actual behavior in practice but rather selfreported counseling frequencies via broad response categories. However, research has indicated that attitudes may be among the most important predictors of behavior [37]. Also, since the response rate was only 53%, attitudes and perceptions of non-respondents may have differed from respondents.…”
Section: Discussionmentioning
confidence: 99%
“…Although research has indicated that childhood healthcare experiences (Pate et al, 1996), healthcare attitudes (Ajzen & Fishbein, 1977), and optimism (Peterson, 2000) are each related to late adolescent health practices, an extensive literature search found no study that has attempted to examine whether the variables might be interrelated to further explain adolescents' healthcare behavior. The identification of predictors of adolescents' healthcare practices should aid in the development of interventions to promote healthy behavior.…”
Section: Introductionmentioning
confidence: 99%
“…23 While some physicians say that they doubt their negative beliefs translate into actions, 24 scores of studies demonstrate that attitudes and intentions often predict behaviors. 25,26 Physicians' attitudes may adversely affect the physicianpatient relationship in a number of meaningful ways. For instance, any increases in hostility and decreases in positive affect may result in physician/patient interaction styles that are lacking in warmth and comfort.…”
Section: Introductionmentioning
confidence: 99%